Lives of Deprivation or Lives of Industry: Possible Cerebral Palsy on the Mary Rose. (April 2015) - Drew, Rose
Contemporary historical and medical writing on impairment in the medieval period claim the disabled were blighted evidence of God's disfavour. Such opinions are often tautologies, unsupported by fourteenth-century primary sources such as Piers Plowman and Lollard writings. Vagrancy proclamations (1495), and dissolution of monasteries from 1538 encouraged self-sufficiency. Impairment may not have equalled poverty.